Development of pre-startup safety review implementation tool for safe operation in process plant - Amiruddin, Abu Bakar; Hanida, Abdul Aziz (Wiley-Blackwell, 2024)
A pre-startup safety review (PSSR) is a formal review of a chemical manufacturing process to verify that critical areas of the affected process have been assessed and addressed before using the process. It can be a new process or after modification to an existing process or operating conditions. There is concern about full implementation compliance, including designing the PSSR program, preparing the process to perform PSSR, following PSSR action items, and approving the PSSR report. This study aims to develop a PSSR Implementation Tool (PSSR-IT) via the Microsoft Excel platform. At the end of the self-assessment process, the end users were provided with the value of the percentage of compliance with PSSR requirements and a thorough review process prior to the start-up activities. A safety experts’ content validation index (CVI) was performed to ensure the tool's content was valid and sufficient for the PSSR process, followed by a case study. Feedback from process safety engineers and PSSR leaders as end users has been collected through the System Usability Scale (SUS). A total of 227 questions have been listed under 10 disciplines, including general info, operation, engineering, operational, process safety, health safety and environment (HSE), action log, final walk down, and approval that cover all essential aspects of review process prior to the start-up activities with CVI value of 0.98, k = 0.67. SUS findings demonstrated that all industrial experts and end users believe the tool is suitable and reliable, with a score >85%. Utilizing the PSSR tool will help the industries promote and improve the process safety program at the workplace.